Verification of the anti-inflammatory activity of the polyphenolic-rich fraction of Araucaria bidwillii Hook. using phytohaemagglutinin-stimulated human peripheral blood mononuclear cells and virtual screening. (15th November 2018) - Talaat, Aya N.; Ebada, Sherif S.; Labib, Rola M.; Esmat, Ahmed; Youssef, Fadia S.; Singab, Abdel Nasser B.
Abstract: Ethnopharmacological relevance: Araucaria bidwillii Hook., the bunya pine, is an evergreen plant belonging to family Araucariaceae. Traditionally, its leaves and oleoresins have been used as herbal remedies to alleviate pain and inflammation. Based upon the frequent adverse effects accompanying synthetic anti-inflammatory drugs, this study will assess the anti-inflammatory activity of both the total methanol extract and the polyphenolic-rich fraction of A. bidwillii leaves. Materials and methods: The anti-inflammatory activity was assessed in vitro using phytohaemagglutinin-stimulated human peripheral blood mononuclear cells (PBMCs). Isolation of the major compounds was conducted using various chromatographic techniques. Molecular modelling studies are performed on tumor necrosis factor-α (TNF-α), cyclooxygenase-II (COX-II) and 5-lipooxygenase (5-LOX). Results: Both the total methanol extract of Araucaria bidwillii leaves and its fraction revealed a dose-dependent manner in lowering the levels of IL-1 β, IL-6 and TNF- α with an equivalent activity to that of indomethacin. In addition, the phytochemical investigation of the polyphenolic-rich fraction results in identification of agathisflavone-4′, 7''-dimethyl ether (1 ), 7- O -methyl-6-hydroxyapigenin (2 ) and 4′, 4′-di- O -methylamentoflavone (3 ) as the main components. In silico molecular modelling showed that agathisflavone-4′, 7''-dimethyl ether (1 ) exhibited the fittest binding in TNF- α active sites, while 7- O -methyl-6-hydroxyapigenin (2 ) showed the highest inhibition in COX-II whereas 4′, 4′-di- O -methylamentoflavone (3 ) is the most potent 5-LOX inhibitor. Conclusion: Thus, the leaves of Araucaria bidwillii could afford a potent anti-inflammatory agent that effectively ameliorates inflammation and its related hazards. This in turn consolidates the fact of using the leaves of Araucaria bidwillii to sooth inflammation in traditional medicine. Graphical abstract: